The role of Gdf5 in the development of the zebrafish fin endoskeleton. Issue 9 (29th July 2021) - Waldmann, Laura; Leyhr, Jake; Zhang, Hanqing; Allalou, Amin; Öhman‐Mägi, Caroline; Haitina, Tatjana
Abstract: Background: The development of the vertebrate limb skeleton requires a complex interaction of multiple factors to facilitate the correct shaping and positioning of bones and joints. Growth and differentiation factor 5 (Gdf5) is involved in patterning appendicular skeletal elements including joints. Expression of gdf5 in zebrafish has been detected in fin mesenchyme condensations and segmentation zones as well as the jaw joint, however, little is known about the functional role of Gdf5 outside of Amniota. Results: We generated CRISPR/Cas9 knockout of gdf5 in zebrafish and analyzed the resulting phenotype at different developmental stages. Homozygous gdf5 mutant zebrafish displayed changes in segmentation of the endoskeletal disc and, as a consequence, loss of posterior radials in the pectoral fins. Mutant fish also displayed disorganization and reduced length of endoskeletal elements in the median fins, while joints and mineralization seemed unaffected. Conclusions: Our study demonstrates the importance of Gdf5 in the development of the zebrafish pectoral and median fin endoskeleton and reveals that the severity of the effect increases from anterior to posterior elements. Our findings are consistent with phenotypes observed in the human and mouse appendicular skeleton in response to Gdf5 knockout, suggesting a broadly conserved role for Gdf5 in Osteichthyes. Key Findings: Generation of zebrafish knockout mutant for the gdf5 gene. The endoskeletal disc segmentation is disrupted, causing posterior radials in the pectoral fins to be lost. Endoskeletal elements in the median fins are disorganized and reduced in length. The severity of the effect increases from anterior to posterior elements.